Phenformin-induced Hypoglycaemia in Normal Subjects - Lyngsoe, J; Trap-Jensen, J (British Medical Journal, 1969)
Study of the effect of phenformin on the blood glucose level in normal subjects before and during 70 hours of starvation showed a statistically significant hypoglycaemic effect after 40 hours of starvation. This effect was not due to increased glucose utilization. Another finding in this study was a statistically significant decrease in total urinary nitrogen excretion during starvation in subjects given phenformin. These findings show that the hypoglycaemic effect of phenformin in starved normal subjects is due to inhibition of gluconeogenesis.